Improving Procedural Text Writing Skills Through the Application of the CIPRO Learning Model in Class VII Students of SMPN 8 Dusun Selatan - Oktabiadaniaty Oktabiadaniaty (FKIP - Universitas Riau, 2026)
The background of the research is the low writing ability of students in writing procedural texts in accordance with the structure and language rules and the low average value of learning Indonesian. This study aims to improve procedural text writing skills through the application of the CIPRO learning model in grade VII students of SMPN 8 Dusun Selatan, South Barito Regency. This research is a Classroom Action Research (CAR) which is carried out in two cycles, each of which consists of the planning stage, action implementation, observation, and reflection. The research subjects were 25 grade VII students. Data collection techniques were carried out through observation, tests, and field notes, while the data analysis technique used qualitative descriptive supported by quantitative data. The results of the study show that the application of the CIPRO learning model can improve students' attitudes, activities, and learning outcomes in writing procedural texts. In cycle I, the average student score reached 72 with a learning completion percentage of 32%. In cycle II, the average score increased to 82 with a learning completion percentage of 88%. Based on these results, it can be concluded that the CIPRO learning model is effective in improving students' procedural text writing skills.